Conflict management, security and intervention in East Asia third-party mediation in regional conflict - Bercovitch, Jacob; Huang, Kwei-Bo; Teng, Chung-Chian (Asian security studies, 2008)
Examines the sources, manifestations and management of conflict in East Asia, which contains many of the world's conflict flashpoints, such as the Korean Peninsula and the China-Taiwan Strait. This book covers: general and NGO approaches to third-party mediation in conflict situations; and, regional conflict management approaches in East Asia.